Farmers' knowledge and perceptions of fall armyworm (Spodoptera frugiperda (J.E. Smith)) damage and factors affecting control method choices in Benin, West Africa - Tossou, T.H.; Sommer, J.H.; Agboton, C.; Adeoti, R.; Tamo, M.; Grundler, F.M.; Borgemeister, C. (2025)
This study examines farmers' knowledge and perceptions of damage caused by fall armyworm (FAW, Spodoptera frugiperda), reports their estimated production losses in southern Benin between 2020 and 2022, and investigates the factors that influenced pest management decisions. A semi-structured questionnaire was used to interview 242 farmers across two agroecological zones of southern Benin from September to December 2023. About 93 % of farmers had broad knowledge of FAW, and 95 % believed they had been affected by infestations and considered the pest dangerous. However, 41 % misinterpreted the timing of FAW attacks, believing that the insect emerged and caused damage only at the mature stage of maize. As a result, synthetic insecticides were frequently applied after significant damage had already occurred. Infestation levels varied across zones: farmers in the Guinean zone reported relatively low infestation (20 %), while those in the Sudano-Guinean zone reported higher levels (40 %), especially in 2021. Yield losses were estimated at 20–40 % during this period. In terms of management, 73 % of farmers relied on synthetic insecticides, 2.5 % adopted cultural practices, 11.6 % used no control methods, and only 1.2 % applied botanical extracts. Further analysis revealed that the choice of FAW control measures was significantly influenced by years of maize farming experience (P < 0.002), financial means (P < 0.001), and to a lesser extent, perceptions of control method effectiveness (P < 0.068). These findings showed that although farmers are aware of FAW, misperceptions about its biology and timing of insecticide application remain problematic. To reduce yield losses, extension programs should prioritize training on the biology of FAW, timing of chemical applications, and consider the aforementioned factors when promoting management practices for FAW control in Benin and similar agroecological contexts.